FRI0179 PREDICTION OF RESPONSE TO RITUXIMAB IN SLE USING A VALIDATED TWO-SCORE SYSTEM FOR INTERFERON. (June 2019) - Alase, Adewonuola; Wigston, Zoe; Burska, Agata; Hensor, Elizabeth; Yusof, Yuzaiful; Reynolds, John; ,; Wittmann, Miriam; Bruce, Ian N.; Vital, Edward
Abstract : Background: Rituximab (RTX) is used for resistant SLE but clinical response varies. We previously validated two interferon-stimulated gene expression scores (IFN-Score-A and IFN-Score-B) that improved prediction of clinical outcomes in SLE. IFN-Score-A included most commonly reported ISGs and predicted flares and glucocorticoid requirements. IFN-Score-B included ISGs that respond to multiple IFN subtypes and predicted development of SLE in At-Risk individuals. Diagnosis of SLE was associated with both scores, while only IFN-Score-B was elevated in RA. The British Society for Rheumatology Biologics Registry (BILAG-BR) collects samples for RTX-treated patients in the UK. MASTERPLANS is a consortium to identify predictors of drug response. Objectives: To investigate whether IFN-Score-A and IFN-Score-B predict BILAG response to RTX at 6 months. Methods: This is a preliminary analysis of the first RTX-treated patients in the BILAG-BR with complete data. Patients were recruited if they were starting a first cycle of RTX for active SLE (BILAG A or 2xBILAG B) despite previous cyclophosphamide or mycophenolate mofetil. Disease activity was measured using BILAG-2004. Clinical response was defined as improvement by >=1 grade in active BILAG-2004 systems with no worsening in other systems. Whole blood was collected into TEMPUS tubes and RNA extracted. IFN-Scores were measured using a custom Taqman array as previously described [El Sherbiny et al., 2018]. Multivariate logistic regression was used to test IFN-Scores and baseline clinical covariates as predictors of BILAG response at 6 months. Results: Samples were available from 147 patients, of whom 84 had complete baseline and 6 month clinical data available and were included in this analysis. 40/84 (47.6%) patients had BILAG response at 6 months. In univariate and multivariate analysis, high IFN-Score-B expression was significantly associated with clinical response (see table 1 ). Conclusion: This preliminary analysis suggests that assessment of IFN activity has a role in predicting response to RTX. A novel IFN score (Score B) was more predictive than classic ISGs (Score A). These results add to a body of work showing that IFN-Score-B predicts clinically significant outcomes independently of overall IFN activity. Future work will analyse this biomarker in a larger cohort of patients and integrate with other putative clinical and biological predictors of response. Reference: [1] El-Sherbiny, Y. M.… E. M. Vital (2018). Sci. Rep. 8: 5793. Acknowledgement: We would like to thank the Medical Research Council, National Institute of Health Research, UK for funding the MASTERPLANS project. Disclosure of Interests: Adewonuola Alase: None declared, Zoe Wigston: None declared, Agata Burska: None declared, Elizabeth Hensor: None declared, Md Yuzaiful Md Yusof: None declared, John Reynolds: None declared, The Masterplans Consortium: None declared, Miriam Wittmann Consultant for: consultancy honoraria from Abbvie, Celgene, Janssen, L'Oreal, Novartis and Pfizer, Ian N. Bruce Grant/research support from: Genzyme Sanofi, GlaxoSmithKline, Consultant for: AstraZeneca, Eli Lilly, GlaxoSmithKline, ILTOO Pharma, MedImmune, Merck Serono, Speakers bureau: GlaxoSmithKline, UCB Pharma, Edward Vital Grant/research support from: He has received honoraria and research grant support from Roche, GSK and AstraZeneca.